Plato's Watermelon: Art and Illusion in The Brothers Bloom - Smith, David L. (The journal of religion and film, 2014)
Rian Johnson’s The Brothers Bloom is a sophisticated film about storytelling, pitting the idea that stories are an enhancement of life against the suspicion that stories are a deception. Set in a world of con artistry and illusion, it raises issues similar to those introduced in Plato’s allegory of the cave and in the critique of religion as illusion. Specifically, it follows one character’s desire for an “unwritten life”—a life free from artifice—through various logical and interpersonal challenges, and ends with a profound meditation on the coinherence of faith and skepticism.